The effect of games and simulations on higher education: a systematic literature review - Vlachopoulos, Dimitrios; Makri, Agoritsa (International Journal of Educational Technology in Higher Education, 2017)
The focus of higher education institutions is the preparation of future professionals. To achieve this aim, innovative teaching methods are often deployed, including games and simulations, which form the subject of this paper. As the field of digital games and simulations is ever maturing, this paper attempts to systematically review the literature relevant to games and simulation pedagogy in higher education. Two researchers collaborate to apply a qualitative method, coding and synthesizing the results using multiple criteria. The main objective is to study the impact of games and simulations with regard to achieving specific learning objectives. On balance, results indicate that games and/or simulations have a positive impact on learning goals. The researchers identify three learning outcomes when integrating games into the learning process: cognitive, behavioural, and affective. As a final step, the authors consolidate evidence for the benefit of academics and practitioners in higher education interested in the efficient use of games and simulations for pedagogical purposes. Such evidence also provides potential options and pathways for future research.